1993
DOI: 10.4319/lo.1993.38.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Wind Influences phytoplankton biomass and composition in a shallow, productive lake

Abstract: Factors that regulate phytoplankton dynamics in shallow, productive lakes are poorly understood. Water-column phytoplankton chlorophyll (avg 105 pg liter-') determined on 39 occasions over a 22-month period in shallow (mean depth, 1.7 m) Lake Apopka, Florida, correlated best with average daily windspeed compared with other environmental variables. High phytoplankton biomass reflects windinduced resuspension of a meroplanktonic algal maximum (MAM) that exists on the aphotic lake bottom in a layer -5 cm thick; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(127 citation statements)
references
References 36 publications
3
121
0
3
Order By: Relevance
“…Thick deposits of unconsolidated flocculent sediments that average Ͼ60% organic matter are present on the lake bottom (Gale and Reddy 1994;Schelske et al 2000). Frequent resuspension of sediments due to wind mixing occurs in this polymictic lake (Carrick et al 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Thick deposits of unconsolidated flocculent sediments that average Ͼ60% organic matter are present on the lake bottom (Gale and Reddy 1994;Schelske et al 2000). Frequent resuspension of sediments due to wind mixing occurs in this polymictic lake (Carrick et al 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The surficial sediments in these areas lost a major structural component of sediment stabilization, thereby becoming more susceptible to resuspension and enhancing diffusive processes. Resuspension and diffusion are known to be potential sources of internal nutrient supply for phytoplankton production (Stumm and Leckie 1971;Bachmann and Jones 1974;Hansen et al 1997) as well as a mechanism for reintroduction of meroplankton into the water column (Carrick et al 1993). Certain unique aspects of the chemistry of the sediments in this region may further enhance the potential for internal nutrient loading.…”
Section: ϫ3mentioning
confidence: 99%
“…Reynolds et al [59] demonstrated that artificial mixing in large enclosures could either prolong diatom dominance or induce new growth for diatoms. Such increases in phytoplankton biomass are related to new growth resulting from resuspended nutrients (such as TP and TN) in lentic waters, where typical mixing episodes in thermally stratified lake systems occur once or twice annually during destratification [2,5,64]. In some lakes, the inhibition of resuspension can decrease the nutrient release from sediments [64], and resuspension is associated with increases in the concentration of phytoplankton biomass and nutrients [27].…”
Section: Photosynthetic Parameters and Cellular Chl A Concentrationmentioning
confidence: 99%